"We need progress, progress has to be made:" Road projects, subaltern politics, and uneven development in Nicaragua. (September 2014) - Alvey, Jennifer
The focus of this article is a rural road building project that was celebrated by its promoters as a dream of historic proportions comes true. The significance of this road project rests not in its length or quality, but in its trajectory or the way it encapsulates processes of neoliberal restructuring that link the rescaling of state, processes of transnational territorial integration, and new spaces and subjects of governance. The road project, its participants and promoters, and the meanings they attributed to it, were informed by a much longer, if already translocal "local" history. But forms of neoliberal transnational governmentality provided a framework that allowed some subaltern actors to at once press for the road and articulate a new politics of place, a larger project that they called "progress." Yet, the very conditions that made the pursuit of progress possible, threatened at every moment to undermine its promise. Thus, this road project provides a unique vantage point for exploring the paradoxes of neoliberal development in terms of longer trajectories of uneven development and subaltern politics.